IoT-driven Environmental Support System for Smart Cities - Andre Kurniawan Pamudji (SISFORMA, 2023)
Smart city is a concept of urban development that integrates information and communication technology (ICT) to enhance efficiency, quality of life, and environmental sustainability. The implementation of smart city has become increasingly popular in the last five years, with many countries developing smart city initiatives, such as the "Smart City Pilot" program in China and the development of smart city applications and platforms in the United States. In Indonesia, several major cities have started developing various digital applications and platforms to improve public service efficiency and encourage economic growth. However, there are still some challenges that need to be addressed, such as inadequate ICT infrastructure, lack of supportive regulations and policies, and insufficient active participation from the community. The use of IoT in smart city plays an important role in collecting real-time data from various connected sensors and devices, allowing for more accurate and timely decision-making. In the long term, this can help improve the overall quality of life of the community. In Indonesia the smart city movement is being intensively implemented by the government with the aim of creating 100 smart cities, so there needs to be efforts made to increase the development of smart cities in Indonesia.